Stress Field Control during Large Caldera-Forming Eruptions - Costa, Antonio; Martí, Joan (Frontiers in Earth Science, 2016)
Crustal stress field can have a significant influence on the way magma is channeled through the crust and erupted explosively at the surface. Large Caldera Forming Eruptions (LCFEs) can erupt hundreds to thousands of cubic kilometers of magma in a relatively short time along fissures under the control of a far-field extensional stress. The associated eruption intensities are estimated in the range 109–1011 kg/s. We analyse syn-eruptive dynamics of LCFEs, by simulating numerically explosive flow of magma through a shallow dyke conduit connected to a shallow magma (3–5 km deep) chamber that in turn is fed by a deeper magma reservoir (>~10 km deep), both under the action of an extensional far-field stress. Results indicate that huge amounts of high viscosity silicic magma (>107 Pa s) can be erupted over timescales of a few to several hours. Our study provides answers to outstanding questions relating to the intensity and duration of catastrophic volcanic eruptions in the past. In addition, it presents far-reaching implications for the understanding of dynamics and intensity of large-magnitude volcanic eruptions on Earth and to highlight the necessity of a future research to advance our knowledge of these rare catastrophic events.